A Comparative Analysis of Gypsies’ Access to Employment Opportunities and Health Services in Pakistan and Turkey - Muhammad Suliman; Reşat Açıkgöz (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Gypsies are an important ethnic group both in Pakistan and Turkey. They are in a more disadvantaged position as compared to other segments of society in areas such as housing, work, health, and education. In this study, employment opportunities and access to health services of gypsies living in Pakistan and Turkey are explored. The researchers delimited the study only to areas of employment and health sectors in both countries, with the aim to comparatively analyze the situation of Gypsies’ access to these services. In the study, qualitative research design and in-depth interview technique were used to collect data from respondents. The interviews were conducted with a total of 14 people (7 participants from Pakistan and 7 from Turkey respectively) including both male and female. According to the findings of the study, Gypsies both in Pakistan and Turkey are mostly excluded from employment opportunities and are pushed to work in informal sectors. Their access to health services is also very limited due to their housing conditions and active lifestyle. However, it has been observed that the conditions of Gypsies in Turkey were found better than the Pakistani ones in terms of employment opportunities and access to health services.